PKM Kelompok Swadaya Masyarakat Tempat Pengolahan Sampah Sehat Sejahtera Di Desa Dutohe Barat Kecamatan Kabila Kabupaten Bone Bolango - Syamsul Syamsul; Muhammad Iqbal Jafar; Syaiful Pakaya (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
The Community Self-Help Group for Reuse, Reduce, and Recycle Waste Processing (TPS3R) Healthy and Prosperous in Dutohe Barat Village, Kabila District, Gorontalo Regency aims to process and utilize the generated household waste so as to provide added economic value and reduce environmental pollution. TPS3R has a scope of services at the Village level which currently serves 156 households out of 543 Family Cards. The types of waste that enter the processing site consist of paper, cardboard, newspapers, cans, plastic cups, glass bottles, plastic bottles, and other organic materials. The problems faced are the lack of understanding of management members in processing types of waste, limited personnel, slow waste sorting process, unorganized work system, no financial bookkeeping, no demand for compost produced by TPS3R. The implementation methods provided are institutional restructuring, training, assistance in the use and manufacture of fertilizers, provision of tools and assistance. The results of the service implementation show the formation of an effective organizational structure and workflow procedures as well as an increase in the number of personnel, increased management understanding in utilizing types of waste, faster sorting because it has been separated from households, financial reports and recording of the amount of waste, there is a request for compost from the household. farmers and households who like ornamental plants.